2015
DOI: 10.1016/j.neuropsychologia.2015.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric lateralization of semantic feature distinctiveness

Abstract: Recent models of semantic memory propose that the semantic representation of concepts is based, in part, on a network of features. In this view, a feature that is distinctive for an object (a zebra has stripes) is processed differently from a feature that is shared across many objects (a zebra has four legs). The goal of this paper is to determine whether there are hemispheric differences in such processing. In a feature verification task, participants responded ‘yes’ or ‘no’ following concepts which were pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
2
7
0
2
Order By: Relevance
“…Second, this effect emerges primarily for natural kinds and is weaker for man-made artifacts. Behaviorally, the results replicate previous findings (Randall, Moss, Rodd, Greer, & Tyler, 2004;Reilly et al, 2015), such that shared features are accessed faster than are distinctive features (this effect was marginally significant in the current results). Furthermore, an interaction emerged between category and feature type.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Second, this effect emerges primarily for natural kinds and is weaker for man-made artifacts. Behaviorally, the results replicate previous findings (Randall, Moss, Rodd, Greer, & Tyler, 2004;Reilly et al, 2015), such that shared features are accessed faster than are distinctive features (this effect was marginally significant in the current results). Furthermore, an interaction emerged between category and feature type.…”
Section: Discussionsupporting
confidence: 90%
“…There was a weak Category × Feature Type interaction, F(1, 15) = 3.51, p = .08, showing a larger effect for natural kinds compared to artifacts, with slightly higher accuracy for distinctive features than for shared features. For reaction times during accurate trials, a 2 × 2 (Category × Feature Type) ANOVA showed a marginal main effect of feature type, F(1, 15) = 3.72, p = .054, such that shared feature responses were faster than distinctive feature responses (see also Reilly et al, 2015). In addition, an interaction emerged, F(1, 15) = 5.88, p = .015, between category and feature type; the shared feature advantage appears to be driven more strongly by artifacts than by natural kinds.…”
Section: Imaging Proceduresmentioning
confidence: 95%
See 2 more Smart Citations
“…En el caso del procesamiento léxico-semántico, se ha descrito una red de lateralización izquierda que se extiende en las regiones temporales inferiores posteriores (Kuperberg, McGuire, Bullmore, Brammer, Rabe-Hesketh, Wright, Lythgoe, Williams & David, 2000;Rodd, Davis & Johnsrude, 2005) y superiores, así como en el giro frontal interior (Perani, Cappa, Schnur, Tettamanti, Collina, Miguel Rosa & Fazio, 1999: 2339. La lateralización funcional del procesamiento semántico involucra de manera más eficiente diferentes redes del hemisferio izquierdo, y marca una clara superioridad sobre la participación del hemisferio derecho en la codificación del significado (Reilly, Machado & Blumstein, 2015). En cercanía a la semántica, la lateralización izquierda también define el procesamiento de los estímulos sintácticos, que activan las áreas frontal y temporal (Vigneau et al, 2011), así como las vías dorsal y ventral entre las cortezas frontal y temporal inferiores del hemisferio izquierdo (Friederici, 2012: 262).…”
Section: Lateralización Y Activación En Los Niveles Específicos Del Punclassified